Analisis system pengendalian manajemen terhadap kinerja manajeman - Kurniawati, Laila Novi (Maliki Interdisciplinary Journal, 2024)
The aim of this paper is to elucidate the findings of an analysis concerning management control systems and their impact on managerial performance. Management control systems are regarded as critical organizational elements in supporting optimal company performance. To achieve success and sustainable growth, companies need to have effective systems and high-quality workforce. One key component of such effective systems is an optimal management control system. Management control systems are utilized by managers to guide organizational members in efficiently and effectively implementing organizational strategies and policies to attain company goals. They serve as tools used by management to enhance company performance, particularly in the context of managerial performance. Additionally, this paper involves a comparison with previous research findings regarding the impact of management control systems on managerial performance. The quality of human resorces is a key factor in the success of an organization or institution, therefore, a careful and selective recruitment process is very important. Organizations that experience rapid growth usually apply strict criteria in selecting staff, with an emphasis on competencies that are in accordance with the goals and direction of the institution. However, human resource development does not stop at the recruitment stage. Advanced islamic educational institutions realize the importance of continuous invesment in employees. They not only pay attention to the welfare aspect, but are also commited to improving the capabilities of staff through various competency and skill improvement programs.